Uso de químicos no reconhecimento sexual de opiliões (Arachnida: Opiliones) - Fernandes, Nathalia da Silva [UNIFESP] (2015)
Several arthropod species use chemicals to detect sexual partners. In harvestmen (Arachnida, Opiliones) there are evidences that chemicals have an important role in intra-specific communication. Using the behavior of Discocyrtus prospicuus (Holmberg 1876) males of exposing the penis to females prior to engaging in mating posture, we tested the following hypotheses: (1) males detect females by contact (chemicals left on the substrate) and (2) males detect females by olfaction. To test hypothesis (1), we submitted males to three experimental groups: female chemicals/white control; male chemicals/white control; female/male chemicals. For hypothesis (2), we allowed that males had access simultaneously to volatiles of males, females and control. We predicted that males would expose the penis when approaching (3 cm) volatiles and chemicals deposited on the substrate by females. We also tested if males spent more time close to the source of female volatiles and, in the case of contact chemoreception, on the substrate with female chemicals. To control for chemical detection without penis exposure, we also tested if males tapped the substrate with female chemicals with the sensory legs I and II for more time than the others. The predictions were refuted, but males did tap for more time the female than the male chemicals. Finally, we put males and females together to observe if males would expose the penis upon touching the female´s cuticle. Our data does not support olfaction as a way to detect females and corroborate the idea that contact chemicals, either left on the substrate or on the female´s cuticle, play an important role in the detection and recognition of the opposite sex. This is the first evidence in Opiliones that males react differently to female/male chemicals.